2006
DOI: 10.1158/1078-0432.ccr-06-1214
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus and Relevant Tumor Suppressors and Oncoproteins in Laryngeal Tumors

Abstract: Purpose: The mechanism of larynx oncogenesis is complex and controlled by various factors, most of them involved in cell proliferation and apoptosis. In this study, we evaluated the levels of two suppressor proteins (pRb and p53) and two oncogenic proteins (c-Myc and Bcl-2), as well as the apoptotic levels and the presence of human papillomavirus (HPV) in both tumor types. Experimental Design: Low-or high-risk HPV viral DNA was determined by PCR and in situ PCR; the level of cellular proteins was examined by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 48 publications
0
34
0
8
Order By: Relevance
“…This was supported by Manjarrez, who showed that in papillomatosis, p53 levels were higher than in normal larynxes, indicating that p53 activity might preserve the apoptosis process. 33 Furthermore, the other apoptosis associated proteins, such as bax, Bak, cmyc and cdc2 were also increased in HPV-11E6 expressed cells compared with control cells.…”
Section: Subcellular Location Of Hpv-11e6 Proteinmentioning
confidence: 92%
“…This was supported by Manjarrez, who showed that in papillomatosis, p53 levels were higher than in normal larynxes, indicating that p53 activity might preserve the apoptosis process. 33 Furthermore, the other apoptosis associated proteins, such as bax, Bak, cmyc and cdc2 were also increased in HPV-11E6 expressed cells compared with control cells.…”
Section: Subcellular Location Of Hpv-11e6 Proteinmentioning
confidence: 92%
“…The following arbitrary restraints were placed on this review; we excluded nonEnglish manuscripts, manuscripts published before 2000, case reports, and investigations using non-PCR techniques or only in-situ PCR. If data were available using multiple techniques, only the PCR-generated data were extracted [1]. Only data generated from primary squamous cell carcinomas (SCC) were extracted, and we excluded reports if: (1) the detection methods were not well-detailed, and/or (2) HPV data could not be extracted per anatomic site.…”
Section: Methodsmentioning
confidence: 99%
“…In Mexico, cervical-uterine cancer (CUC) is the most frequent sexually transmitted viral disease and cause of death in women older than 25 years [3,4]. A link between HPV and squamous cell carcinoma of the head and neck was suggested more than 20 years ago [5]. Investigators showed a strong association between high-risk HPV infection and oral squamous cell carcinoma in Mexican, Sweden Japanese, and Chinese populations [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A link between HPV and squamous cell carcinoma of the head and neck was suggested more than 20 years ago [5]. Investigators showed a strong association between high-risk HPV infection and oral squamous cell carcinoma in Mexican, Sweden Japanese, and Chinese populations [5][6][7][8]. So HPV infection is not limited to the genital tract; it can extend to extragenital sites and particularly to the oral cavity, but the mechanism of infection of HPV into the oral mucosa remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation